Analysis of the Effects of Parameters on Alloy Steel during Computer Numeric Control (CNC) Turning - Jangra, Sachin; Gupta, Mukesh; Kumar, Raj (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
Turning is one of the important manufacturing processes used now days. Metal is removed in the form of chips. In turning work piece is kept stationary (but rotates) while tool moves along the axis of rotation. CNC turning machine is controlled by various process parameters and the cutting conditions to get efficient work. This Study aims to find the relation between those process parameters on the output parameters like MRR, Surface finish etc. The most common parameters controlling the processes are speed, feed, depth of cut, tool geometry, coolant, work material etc. Analyzing these effects also helps in optimizing the parameters to get work efficiently. Various techniques are available for solving such type of problems out of which Taguchi method is the most widely used technique for the optimization.